MongoDB Clustering using K-means for Real-Time Song Recognition - Murtadha Arif Sahbudin; Marco Scarpa; Salvatore Serrano (IEEE, 2024)
Date of Conference: 18-21 February 2019 INSPEC Accession Number: 18600816 Conference Location: Honolulu, HI, USA